Quinacrine Has Preferential Anticancer Effects on Mesothelioma Cells With Inactivating NF2 Mutations - Oien, Derek B.; Sarkar Bhattacharya, Sayantani; Chien, Jeremy; Molina, Julian; Shridhar, Viji (Frontiers in Pharmacology, 2021)
Mesothelioma is a rare cancer with disproportionately higher death rates for shipping and mining populations. These patients have few treatment options, which can be partially attributed to limited chemotherapy responses for tumors. We initially hypothesized that quinacrine could be combined with cisplatin or pemetrexed to synergistically eliminate mesothelioma cells. The combination with cisplatin resulted in synergistic cell death and the combination with pemetrexed was not synergistic, although novel artificially-generated pemetrexed-resistant cells were more sensitive to quinacrine. Unexpectedly, we discovered cells with NF2 mutations were very sensitive to quinacrine. This change of quinacrine sensitivity was confirmed by NF2 ectopic expression and knockdown in NF2 mutant and wildtype cell lines, respectively. There are few common mutations in mesothelioma and inactivating NF2 mutations are present in up to 60% of these tumors. We found quinacrine alters the expression of over 3000 genes in NF2-mutated cells that were significantly different than quinacrine-induced changes in NF2 wildtype cells. Changes to NF2/hippo pathway biomarkers were validated at the mRNA and protein levels. Additionally, quinacrine induces a G1 phase cell cycle arrest in NF2-mutated cells versus the S phase arrest in NF2-wildtype cells. This study suggests quinacrine may have repurposing potential for a large subset of mesothelioma patients.